TiO2 material loaded on LDH/MIL-101(Fe) is doped with La and Fe to effectively remove pyridine: “Performance and mechanism” - Wei Zhang; Ku Yu; Wang Aihe (Results in Chemistry, 2025)
In this study, pyridine-a representative nitrogen-containing heterrocylic contaminant in coal chemical wastewater-was targeted for photocatalytic degradation. We developed a novel ternary composite photocatalyst through the in-situ integration of layered double hydroxide (LDH) and iron-based metal-organic framework (MIL-101(Fe)) with lanthanum‑iron co-doped TiO2 via hydrothermal synthesis. These contaminants are characterized by high environmental persistence, low biodegradability, and potential teratogenic/carcinogenic risks. The synthesized LDH/MIL-101(Fe)/La-Fe-TiO2 composite was systematically characterized using scanning electron microscopy (SEM), UV–Vis diffuse reflectance spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS), and Brunauer-Emmett-Teller (BET) analysis. Key findings revealed that: (1) The composite architecture achieves an exceptional specific surface area of 168.96 m2/g through synergistic LDH/MIL-101(Fe) integration; (2) La–Fe co-doping effectively extends the photoresponse threshold of TiO2 to the visible-light region. Under optimized conditions (25 °C, 300 rpm agitation, 400 W irradiation), the system achieved 96.1 % pyridine degradation (initial concentration: 100 mg/L) within 4 h, following pseudo-first-order kinetics (R2 = 0.99). Remarkably, the catalyst maintained 94.5 % efficiency after five consecutive cycles, demonstrating superior stability. Mechanistic investigations combining GC–MS analysis, electron paramagnetic resonance (EPR) detection, and radical quenching tests identified the reactive species activity sequence as ∙h+ >∙OH> O2−, ultimately elucidating the complete pyridine mineralization pathway.